2014
DOI: 10.1371/journal.pone.0101899
|View full text |Cite
|
Sign up to set email alerts
|

miR-141 and miR-200c as Markers of Overall Survival in Early Stage Non-Small Cell Lung Cancer Adenocarcinoma

Abstract: BackgroundSeveral treatments in non-small cell lung cancer (NSCLC) are histology-dependent, and the need for histology-related markers is increasing. MicroRNAs (miRNAs) are promising molecular markers in multiple cancers and show differences in expression depending on histological subtype. The miRNA family miR-200 has been associated with the regulation of epithelial-mesenchymal (EMT)/mesenchymal-epithelial transition (MET). EMT involves profound phenotypic changes that include the loss of cell-cell adhesion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 36 publications
(41 reference statements)
5
88
1
Order By: Relevance
“…To the best of our knowledge, there have been only 4 clinical studies on miR-200c expression in NSCLC to date, producing contradictory results (i.e. that miR-200c has been reported to have oncogenic or tumor-suppressive functions) (10,12,22,23). The present study aimed to assess miR-200c expression in NSCLC, and to investigate the role of miR-200c in relation to carcinogenesis and the prognosis of NSCLC patients.…”
Section: Discussionmentioning
confidence: 96%
“…To the best of our knowledge, there have been only 4 clinical studies on miR-200c expression in NSCLC to date, producing contradictory results (i.e. that miR-200c has been reported to have oncogenic or tumor-suppressive functions) (10,12,22,23). The present study aimed to assess miR-200c expression in NSCLC, and to investigate the role of miR-200c in relation to carcinogenesis and the prognosis of NSCLC patients.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it was also shown that the expression level of miR-141 was associated with cancerspecific survival. Tejero et al (2014) found that high miR-141 expression was associated with shorter overall survival in patients with non-small cell lung cancer (NSCLC). Gao and Wu (2015) found that serum miR-141 levels were significantly elevated in epithelial ovarian cancer patients compared to healthy controls, and patients with low miR-141 levels showed a significantly higher rate of survival.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian and breast cancer patients showing incomplete response to paclitaxel treatment expressed low levels of miR-200c along with significant increase in beta-tubulin and ZEB1 expression when compared with patients showing complete response to paclitaxel [109,118]. Furthermore, in NSCLC patients, high expression of miR-200c has been found to be correlated with bigger tumor size and worse overall survival suggesting an oncogenic activity of miR-200c [114,115]. In terms of tumor subtype classification, oncocytoma and chromophobe structures in renal tumors can be distinguished according to miR200c and miR-139-5p expression patterns [121].…”
Section: Mir-200c As a Biomarkermentioning
confidence: 99%